2005
DOI: 10.1001/archsurg.140.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Peritoneal Inflammatory Mediators in Children With Suspected Acute Appendicitis

Abstract: Hypothesis: Inflammatory markers differ between subjects with appendicitis and controls. Markers of inflammation differ in serum compared with intraperitoneal fluid. Among subjects with appendicitis, inflammatory markers differ between subjects with and without perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 21 publications
2
30
0
2
Order By: Relevance
“…There are little and controversial data about the use of G-CSF in AA diagnosis. Dalal et al reported that there is not any significant increase in levels of G-CSF in AA [9]. In contrast, Allister et al found that when compared to normal population, in AA G-CSF levels increase significantly [10].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are little and controversial data about the use of G-CSF in AA diagnosis. Dalal et al reported that there is not any significant increase in levels of G-CSF in AA [9]. In contrast, Allister et al found that when compared to normal population, in AA G-CSF levels increase significantly [10].…”
Section: Discussionmentioning
confidence: 95%
“…There is little data about the use of G-CSF in diagnosis of AA [9]. In a study, it is found to be useful in staging of AA [10].…”
Section: Introductionmentioning
confidence: 99%
“…It may be raised in 50-90% of patients with acute appendicitis but again it is non-specific. Serum levels of inflammatory markers including CRP and WBC count cannot be reliably used to distinguish between acute appendicitis and other causes of abdominal pain (Dalal et al, 2005). They are more effective in supporting a clinical diagnosis of appendicitis than excluding the diagnosis (Birchley, 2006).…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Thus, a safe guess, which is done in preoperative way, ranges froma possible surgery to morbidity and mortality which are relevant to surgery. Different infl ammatory indicators (White blood cell (WBC), C-reactive protein (CRP) (4), D-lactate level (5), level of calprotectin (6), level of procaltinonin (7), many interleukins (8) and usage of monitoring methods in diagnosis of appendicitis are available in many studies related to discrimination of complicated/non complicated. Neutrophil and lymphocyte ratio (NLR) starts to fi nd place for itself recently between these indicators (9).…”
Section: Introductionmentioning
confidence: 99%